1993
DOI: 10.1128/mcb.13.8.5020
|View full text |Cite
|
Sign up to set email alerts
|

Selective and synchronous activation of early-S-phase replicons of Ehrlich ascites cells.

Abstract: Twelve-hour exposure of G1 Ehrlich ascites cells to controlled hypoxia (200 ppm of 02 at 1 bar) suppressed replicon initiation. Synchronous cycling, beginning with a normal S phase, was released by reoxygenation immediately. The addition of cycloheximide at reoxygenation largely resuppressed, after a short initial burst, succeeding replicon initiations. Alkaline sedimentation analysis of growing daughter strand DNA, DNA fiber autoradiography, and analysis of the newly formed DNA demonstrated that normal chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…DNA synthesis in AG1522 cells immediately after reoxygenation occurred both in cells emerging from G1 phase and also in cells that had a greater than GI-phase content of DNA, indicating that under hypoxia, some cells in S phase stopped synthesizing DNA and, upon reoxygenation, restarted where they had stopped. This is consistent with previously published results and is thought to reflect a lack of replicon initiation under hypoxia (20,62). GM02184B cells differed from AG1522 cells in that they lacked any DNA synthesis in the first 4 h following reoxygenation (Fig.…”
Section: Resultssupporting
confidence: 82%
“…DNA synthesis in AG1522 cells immediately after reoxygenation occurred both in cells emerging from G1 phase and also in cells that had a greater than GI-phase content of DNA, indicating that under hypoxia, some cells in S phase stopped synthesizing DNA and, upon reoxygenation, restarted where they had stopped. This is consistent with previously published results and is thought to reflect a lack of replicon initiation under hypoxia (20,62). GM02184B cells differed from AG1522 cells in that they lacked any DNA synthesis in the first 4 h following reoxygenation (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Some studies have suggested that DNA initiation is affected by hypoxia and is most apparent at low oxygen tensions (21,42,43,46,47). Alternatively, deoxynucleotide depletion, which would be expected to affect DNA initiation, as well as elongation, has also been suggested to occur in hypoxic cells (9,37).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most cells are able to resume DNA synthesis within 10 min to 3 h after reoxygenation (38). However, little information is known about the genetic determinants that govern the reentry of hypoxic cells into the cell cycle except that recovery of DNA synthesis is blocked by cycloheximide addition in Ehrlich ascites cells (11,32) and is associated with the appearance of hyperphosphorylated pRb in T-47D breast cancer cells (2).…”
mentioning
confidence: 99%
“…Studies using alkaline sedimentation analysis and fiber autoradiography have revealed that replicon initiation is suppressed by severe oxygen deprivation, but chain elongation and maturation continue normally for at least a few hours (11,29,32). While the persistence of chain elongation under hypoxic conditions implies that the lack of precursors is not directly responsible for the failure to synthesize DNA, it has been proposed that the nucleotide imbalance caused by hypoxia can act as a signal leading to cessation of replication (32).…”
mentioning
confidence: 99%